TO DEDUCE THE CHANGES IN LIPID PROFILE AND BMI, THAT LEADS TO CARDIOVASCULAR DISEASES IN POSTMENOPAUSAL WOMEN - Kiran Lohana; Jai Parkash; Muhammad Zain Shaikh; Mubashir Ghani; Naina lohana; Dr Arsalan Ahmed Uqaili (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
Aim: The present observation, case report study was conducted during the period of one year in Hyderabad to observe the changes in the lipid profile of postmenopausal women that make them vulnerable to cardiovascular diseases. Materials and Methods: Venous blood samples of 320 postmenopausal women were taken to see changes in lipid profile. Lifestyle and food habits were noted by filling out the questionnaire. Women with diagnosed cardiovascular diseases, on hormone replacement therapy or lipid-lowering drugs, were excluded from the study. Results: Weight, BMI, and stature ranged greatly between groups. Body changes after menopause; overweight women had higher weight, BMI, and height than normal women. Both normal-weight and overweight postmenopausal women had considerable lipid changes. Postmenopausal women of normal weight had lower HDL cholesterol, higher LDL cholesterol, and increased total cholesterol and triglycerides. VLDL levels did not decrease (p > 0.05), but other lipid fractions did, suggesting cardiovascular risk in this cohort. Conclusion: Studies show that unfavorable lipid alterations at this age increase cardiovascular disease risk. Postmenopausal women must regulate lipids to reduce risk and improve cardiovascular health.